Military finances personal money management for service members, veterans and their families - Lawhorne-Scott, Cheryl 1968-; Philpott, Don 1946- (Military life, 2013)
Military Finances is essential reading for any soldier, veteran, or military family member concerned with their financial future. Members of the military often have a tough time handling their finances, whether it be while serving active duty or when returning to civilian life; and our uncertain economy and job market only magnify those issues. Many serving in the military are young, with little or no training in financial affairs, and face frequent deployments and relocations-all of which can wreak havoc on a person's finances.